Complement lectin pathway components MBL and MASP-1 promote haemostasis upon vessel injury in a microvascular bleeding model - Golomingi, Murielle; Kohler, Jessie; Jenny, Lorenz; Hardy, Elaissa T.; Dobó, József; Gál, Péter; Pál, Gábor; Kiss, Bence; Lam, Wilbur A.; Schroeder, Verena (Frontiers in Immunology, 2022)
Background: Complement lectin pathway components, in particular mannan-binding lectin (MBL) and MBL-associated serine proteases (MASPs) have been shown to interact with coagulation factors and contribute to clot formation. Here we investigated the role of MBL and MASP-1 in the haemostatic response following mechanical vessel injury in a human microfluidic bleeding model. Methods: We studied haemostasis in a microvascular bleeding model in the presence of human endothelial cells and human whole blood under flow conditions. We monitored incorporation of proteins into the clot with fluorescently labelled antibodies and studied their effects on clot formation, platelet activation, and bleeding time with specific inhibitors. Platelet activation was also studied by flow cytometry. Results: Upon vessel injury, MBL accumulated at the injury site in a well-defined “wall-like” structure. MBL showed partial colocalisation with fibrin, and strong colocalisation with von Willebrand factor and (activated) platelets. Flow cytometry ruled out direct binding of MBL to platelets, but confirmed a PAR4- and thrombin-dependent platelet-activating function of MASP-1. Inhibiting MBL during haemostasis reduced platelet activation, while inhibiting MASP-1 reduced platelet activation, fibrin deposition and prolonged bleeding time. Conclusion: We show in a microvascular human bleeding model that MBL and MASP-1 have important roles in the haemostatic response triggered by mechanical vessel injury: MBL recognizes the injury site, while MASP-1 increases fibrin formation, platelet activation and shortens bleeding time. While the complement lectin pathway may be harmful in the context of pathological thrombosis, it appears to be beneficial during the physiological coagulation response by supporting the crucial haemostatic system.